#1**0 **

...Is this some trick question?

Statement 8 is incorrect...It claims 2 = 1...

Besides, qeustions not related to math should be considered "off-topic"...

PartialMathematician Nov 20, 2018

#4**+1 **

The fallacy is the transition from Step 4 to Step 5

4 (a + b) ( a - b) = b ( a - b)

But if a = b.....then we have

5 (a + b) ( 0) = b ( 0)

So....6 becomes

0 = 0 which is the logical conclusion, not " a + a = a "

CPhill Nov 21, 2018

#6**0 **

If \(a=b=0\), technically 0 + 0 = 0 is correct, and (0+0)(0-0) does equal 0(0-0).

PartialMathematician
Nov 21, 2018